Active surveillance in small renal masses - Luangtangvarodom, Phawat; Sowanthip, Dutsadee (Insight Urology, 2022)
Active surveillance is one of the options available for management of renal masses smaller than 4 cm with a suspicion of malignancy in association with nephrectomy and ablative procedures. In general, small renal masses grow slowly and have a very low metastatic potential, but exceptions occur. Active surveillance is generally offered in the elderly with high comorbidities but there is a lack of validated data in other patient demographics. Data from younger and healthier patients are gradually emerging and have shown promising results but still require further validation. Computed tomography (CT), magnetic resonance imagin (MRI), and ultrasonography (US) are all acceptable imaging modalities for surveillance of renal masses, but CT is the most commonly used. Intervals of surveillance differs from study to study, but the most common schedule is 3, 6, and 12 months after initiation, then annually. The cut off point for delayed intervention is growth > 0.5 cm/year or absolute size > 4 cm. Oncologic outcome is comparable to nephrectomy and ablation in terms of cancer-specific survival. Quality of life for patients undergoing active surveillance is also comparable but is significantly lower in those with confirmed malignant biopsy results. Cost of active surveillance is as a rule more cost effective than nephrectomy or ablation.